Effect of Various Intermittent Fasting Protocols on Hyperglycemia-Induced Cognitive Dysfunction in Rats - Hani A. Alfheeaid; Ahmad A. Alhowail; Faiyaz Ahmed; Abdel Kader A. Zaki; Areej Alkhaldy (Brain Sciences, 2023)
Diabetes mellitus is a highly prevalent metabolic disorder that causes cognitive decline. Here, we investigated the impact of various intermittent fasting protocols on type 2 diabetes mellitus (T2DM)-induced cognitive dysfunction in a rodent model. Male Sprague–Dawley rats (aged 3 months) were randomly assigned to five groups (n = 6 per group) and T2DM was induced by streptozotocin (60 mg/kg, IM). The control group was untreated. Cognitive function was tested (Y-maze, novel object recognition, and elevated plus maze tests) and glucose was assessed. The T2DM rats exhibited significantly higher blood glucose, which is associated with cognitive dysfunction. Compared to the validated animal model of T2DM in rats, various intermittent fasting protocols decreased blood glucose and improved cognitive function. These results indicate that various intermittent fasting protocols may be a potential strategy for managing the hyperglycemia-associated cognitive dysfunction.